Marketing Strategy for Korean Consumer Goods among Young Consumers in Ho Chi Minh City – Identifying Determinants of Purchase Decision - Pham, Ngan Vu Thien; Ton, Han Nu Ngoc (Review of Integrative Business and Economics Research, 2023)
[...]Hallyu, social media, and other factors positively affected product decisions at different levels of significance. In line with the prescribed objectives, the study intends to provide answers to the following questions: * How do Hallyu, social media, country of origin, and their related elements influence Ho Chi Minh youngsters'purchase decisions of Korean consumer goods? * How can international marketers promote purchase decisions of Korean consumer goods among Vietnamese young people? According to Das (2015), perceived quality is a strategic tool to drive customer willingness to perform a purchasing behavior in the retail industry, especially for female groups who are more conscious of quality-driven factors than their male counterparts. 2.2.2 Hallyu and attitudes Hallyu wave (also known as the Korean wave) reflects the growing global popularity of Korean cultures, such as K-pop, K-movies, K-dramas, and K-entertainment (Jin & Yoon, 2016). According to Purnawirawan et al.'s (2012) empirical study, online reviews in social media facilitate consumers'perceived usefulness regarding the purchase of products recommended by other users.